Les Quinze à la croisée des chemins. Sur les formes possibles de l'Union européenne - Bouchard, Lucien-Pierre (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1996)
The European Union (EU) does not typify any of the political union models that were proposed for the basis of Us formulation. Quite to the contrary, the Maastricht Treaty interweaves components of these prototypes, with the end result being rather disconcerting at a conceptual level. The Treaty does stipulate, however, that an Intergovernmental Conference take place in 1996-97; an important item on the agenda mil be defining the political union model that will set the stage for further European integration. This paper identifies and analyses the alternative political union models available to EU members, and attempts to discern which of them will, in most likelihood, be selected by the Conference. They are grouped into jour categories: status quo, federation, renationalisation and confederation. These models, each in their unique style, address such issues as alleviating the democratic deficit (explored further in paper) and buttressing the legitimacy of Brussells' institutions. The paper suggests that the Conference will ultimately choose between the status quo and confederation options ; but, faced with the difficulty of predicting which of these choices will win favour - especially given the debate unfolding on eastern EU expansion - it does not attempt to pinpoint the outcome of the Conference. It does conclude, however, that the renationalisation and federation options are not realistic in light of their weak foothold in Europeans' political culture.